Usmerjanje urbanega razvoja na mestni ravni - Šašek-Divjak, Mojca (Urbani izziv, 1999)
As emphasised in the present plan of Copenhagen, the town plan can not solve all urban problems. It should represent a proposed order, that often crumbles because of unexpected spatial events. Problems are often solved only when they appear. Therefore a town plan has to be concieved as flexible and adoptable, allowing necessary change. It must nevertheless give a town strong basic guidelines and thus enable th inhabitants to use opportunities given by the new era to enforce dwelling qualities.
Keywords: Kopenhagen; mestni načrti; prostorski razvoj; urbani razvoj; urbanism; urbanizem